TEACHER'S STRATEGY IN EFFECTIVE LEARNING THROUGH CALENDAR GAMES IN EARLY CHILDREN - Suhada Suhada (JUMPA : Jurnal Manajemen Pendidikan, 2022)
This study aims to discover teacher strategies for making learning effective through calendar games in early childhood at RA Bustanul Ulum Liprak Wetan, Probolinggo Regency. This study uses a qualitative approach to the type of Classroom Action Research, which consists of three cycles. Each cycle includes planning, action, observation, and reflection. The results showed that the teacher's strategy in making learning effective through calendar games in early childhood at RA Bustanul Ulum Liprak Wetan, Probolinggo Regency, could improve the cognitive ability to recognize the concept of numbers in children at RA Bustanul Ulum Liprak Wetan, Probolinggo. Learning through the media of counting trees can improve cognitive abilities in recognizing children's numbers marked by an increase in each cycle, namely Cycle I, 55%, and Cycle II, 86%.